Efficient High GainYtterbium Doped Lead Fluoroborate Glasses Fiber Amplifiers - Dagher, AbdulKareem H. (University of Thi-Qar Journal of Science, 2014)
This paper is based on the numerical solution of the rate equations model and their gain dependences are discussed. Simulation of the amplifier gain versus the pump power, amplifier length, ion concentration and core radius has been done. In order to keep the fiber amplifiers doped with ytterbium as short as possible with high gain, it is best to increase the doped concentration. For 10m amplifier length, pump power of 25mW, core radius of 2.5mm and 3 ion/m 25 3.5´10 doping concentration, the gain is 60dB. Increasing of the core radius would increase the threshold pump power and at the above same conditions, the optimum gain is at 5mm core radius.